Meningkatkan kemampuan berbicara bahasa Arab siswa madrasah tsanawiyah menggunakan media visual - Anna Saraswati; Laily Maziyah; Mohammad Ahsanuddin (Universitas Pendidikan Indonesia, 2026)
The teaching of Arabic in Islamic schools continues to face difficulties in fostering students’ speaking proficiency (maharah al-kalam). This situation largely stems from the limited provision of authentic oral practice within conventional, teacher-dominated classroom settings. This condition causes students to lack confidence and to be passive in their use of Arabic for communication. This study examines the use of visual media, specifically animated videos and picture cards, to improve students' speaking skills in Arabic Language Learning. The research employed a descriptive qualitative method, involving 34 students from class VIII.3 at MTs Negeri 1 Kota Tangerang Selatan as research participants. Data collected through observation, interviews, and documentation were then analyzed using Miles and Huberman's interactive model. The results showed that animated videos increased students' learning motivation, understanding of the material, and pronunciation accuracy through authentic visual and auditory contexts. Meanwhile, picture cards facilitated active interaction, enriched understanding, and fostered students' confidence in speaking. The integration of the two media strengthened linguistic comprehension, encouraged emotional engagement, and promoted effective collaborative learning.